2018
DOI: 10.1002/cam4.1506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of paranasal sinus invasion on advanced nasopharyngeal carcinoma treated with intensity‐modulated radiation therapy: the validity of advanced T stage of AJCC/UICC eighth edition staging system

Abstract: The aim of this study was to clarify the prognostic role of paranasal sinus invasion in advanced NPC patients. Data of patients (n = 295) with advanced NPC (T3/T4N0‐3 M0) treated with intensity‐modulated radiation therapy were retrospectively analyzed. Staging was according to the AJCC/UICC eighth edition staging system. Overall survival (OS), local recurrence‐free survival (LRFS), distant metastasis‐free survival (DMFS), and disease‐free survival (DFS) were calculated, and differences were compared between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Similar results were found by Cao et al (8). Another study showed that classification of PSI into T4 provided better distinction between T3 and T4 in all survival outcomes (18). Our study demonstrated the independent prognostic value of PSI after ruling out the confounding of T4 structures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were found by Cao et al (8). Another study showed that classification of PSI into T4 provided better distinction between T3 and T4 in all survival outcomes (18). Our study demonstrated the independent prognostic value of PSI after ruling out the confounding of T4 structures.…”
Section: Discussionsupporting
confidence: 91%
“…PSI is not rare in NPC. Previously reported incidence of PSI ranged from 16.0% (17) to 42.7% (18) in locally advanced NPC. However, most of studies included both T3 and T4 patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, survival data were only obtained for 3 years in the study by Zhang et al, and all of the studies above used the seventh AJCC staging system. Wang et al 19 retrospectively analyzed 295 advanced NPC patients who underwent IMRT based on the eighth AJCC staging system. Patients without paranasal sinus invasion had better OS, LRFS, DMFS, and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…NPC with paranasal sinus invasion is considered T3 classification in the eighth edition of the AJCC staging system, whereas the Chinese 2008 staging system, which is widely used in southern China, defines it as T4 disease . There are limited studies about the prognostic value and staging classification of NPC with paranasal sinus invasion, especially in the IMRT era with the current AJCC staging system . Whether different types of paranasal sinus invasion should be classified as the same T classification is still controversial .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation